2003
DOI: 10.1002/app.12393
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐exchange resins. II. Acrylamide crosslinked copolymers as precursors for some ion exchangers

Abstract: Crosslinked copolymers of acrylamide (AA) and ethylacrylate and some ion exchangers derived from them containing either primary amine groups, obtained by the Hofmann degradation of the amide groups, or carboxylic groups, obtained by the alkaline hydrolysis of the ester groups, were studied. Divinylbenzene and N,NЈ-methylenebisacrylamide were used as crosslinkers. The starting copolymers and the corresponding ion exchangers were characterized by IR spectroscopy, swelling behavior, and thermogravimetric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Th e water uptake dependence on the copolymer structure gave information on the hydrophilicity of these copolymers. Crosslinked copolymers of AA and EA and some ion exchangers derived from them containing either primary amine groups or carboxylic groups were studied by Dragan et al [136], where DVB and MBAA were used as crosslinkers. Th e copolymers and the corresponding ion exchangers were characterized by IR spectroscopy, swelling behavior and thermogravimetric analysis.…”
Section: Crosslinking Monomer(s)mentioning
confidence: 99%
“…Th e water uptake dependence on the copolymer structure gave information on the hydrophilicity of these copolymers. Crosslinked copolymers of AA and EA and some ion exchangers derived from them containing either primary amine groups or carboxylic groups were studied by Dragan et al [136], where DVB and MBAA were used as crosslinkers. Th e copolymers and the corresponding ion exchangers were characterized by IR spectroscopy, swelling behavior and thermogravimetric analysis.…”
Section: Crosslinking Monomer(s)mentioning
confidence: 99%
“…They determined the degree of crosslinking by γ -irradiation, extraction and swelling experiments. Vlad and co-workers [8] correlated the synthesis conditions of the acrylamide co-polymers with the properties of the ion exchangers derived from them, using divinylbenzene and N ,N -methylenebis acrylamide as cross-linker. It was observed that the structural changes in acrylamide co-polymers took place on account of the chemical reactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The water uptake in dependence on the co-polymer structure gave information on the hydrophilicity of these co-polymers. Cross-linked co-polymers of acrylamide (AM) and ethylacrylate and some ion exchangers derived from them containing either primary amine groups or carboxylic groups were also studied by Dragan et al [8]. Divinyl benzene and N ,N -methylenebis acrylamide were used as cross-linkers.…”
Section: Cross-linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional copolymers, linear and crosslinked, bearing primary amine groups are of great interest because of their high reactivity, which allows the incorporation of numerous additional moieties. 3 However, ion exchangers with primary amine groups are difficult to obtain by chemical reactions with St-DVB copolymers.…”
Section: Introductionmentioning
confidence: 99%